INVESTIGATING FACTORS AFFECTING ON ENGLISH READING PERFORMANCE OF URDU AND SINDHI HIGHER SECONDARY SCHOOL LEARNERS IN THE PAKISTANI CONTEXT - Hassaan Ahmed (`, 2024)
The current study investigated how Pakistani Urdu & Sindhi high school students’ English reading performance was influenced by their family background, educational background, and prior language learning experiences. Additionally, this study also demonstrated how differences in home backgrounds, educational backgrounds, and prior language learning experiences among Urdu and Sindhi high school students affected their English reading performance. The qualitative research methodology was modified for the exploratory study. To get a clear picture of the phenomena, the data was gathered through in-depth semi-structured interviews with a small number of participants. The data were evaluated from eight students: four learners from the Urdu group and four from the Sindhi group. The data was analyzed by using thematic analysis. Finally, the results were collected for the outcome of the study. The findings indicated that the development of reading performance as a whole is significantly influenced by home setting, educational background, and prior language learning experiences. Second, high school learners do not have strong family background, a solid educational foundation, and good prior language learning experiences. These factors are responsible for the poor performance in reading. Moreover, in comparison to Urdu & Sindhi learners: Urdu learners have better home backgrounds, educational backgrounds, and past language learning experiences than Sindhi students. Keywords: English Reading Performance, Home Background, Educational Background, Past Language Learning Experiences, Urdu & Sindhi Learners, Higher Secondary School Learners. https://doi.org/10.5281/zenodo.19738061